The effect of acetaminophen on the expression of BCRP in trophoblast cells impairs the placental barrier to bile acids during maternal cholestasis - Blazquez, Alba G. (2014)
Acetaminophen is used as first-choice drug for pain relief during pregnancy. Here we have investigated the effect of acetaminophen at subtoxic doses on the expression of ABC export pumps in trophoblast cells and its functional repercussion on the placental barrier during maternal cholestasis. The incubation of human choriocarcinoma cells (JAr, JEG-3 and BeWo) with acetaminophen for 48h resulted in no significant changes in the expression and/or activity of MDR1 and MRPs. In contrast, in JEG-3 cells, BCRP mRNA, protein, and transport activity were reduced. In rat placenta, collected at term, acetaminophen administration for the last three days of pregnancy resulted in enhanced mRNA, but not protein, levels of Mrp1 and Bcrp. In fact, a decrease in Bcrp protein was found. Using in situ perfused rat placenta, a reduction in the Bcrp-dependent fetal-to-maternal bile acid transport after treating the dams with acetaminophen was found. Complete biliary obstruction in pregnant rats induced a significant bile acid accumulation in fetal serum and tissues, which was further enhanced when the mothers were treated with acetaminophen. This drug induced increased ROS production in JEG-3 cells and decreased the total glutathione content in rat placenta. Moreover, the NRF2 pathway was activated in JEG-3 cells as shown by an increase in nuclear NRF2 levels and an up-regulation of NRF2 target genes, NQO1 and HMOX-1, which was not observed in rat placenta. In conclusion, acetaminophen induces in placenta oxidative stress and a down-regulation of BCRP/Bcrp, which may impair the placental barrier to bile acids during maternal cholestasis.